(untitled) (AYUSHDHARA, 2017)
In the context of Vata Vyadhi Acharyas explain about a painful condition afflicting the lower limbs called ‘Grdhrasi’, Where in the pain from low back gradually radiating towards the regions of the posterior aspect of Kati, Uru, Jaanu, Jangha and Pada is the opinion of Acharya Caraka, but Acharya Sushruta and Acharya Vagbata opines that there are two Kandara in the leg that gets afflicted (Tendons of the feet getting vitiated) by Vata which causes pain radiating towards the ankles or toes is called as Grdhrasi. These two Kandara when gets afflicted with the Vata Dosha limits the extension of the leg. This condition is similar with sciatica which refers to the Radiating pain from low back to lower limb as the typical characteristic feature of this illness. A case report with the presenting complaints of shooting type of pain from low back pain radiating to both the lower limbs posteriorly till the toes (more towards the right lower limb) since six months. As a treatment measure, Vaitarana Basti was selected which showed good result and helped to relieve the impairment of the patient in her daily activities. This article explains about the action of Vaitarana Basti in Grdhrasi.